Commodities rising : the reality behind the hype and how to really profit in the commodities market - Christian, Jeffrey M., 1955- (Wiley, 2006)
Analyze the current commodity environment and look out over the next few years to identify potential profit situations in Commodities Rising. You'll learn how commodities can be used to reduce risk and increase returns in a balanced investment portfolio.